Low cost bifunctional initiators for bidirectional living cationic polymerization of olefins. I. isobutylene. Issue 22 (3rd September 2017) - Nugay, Turgut; Keszler, Balazs L.; Deodhar, Tejal; Nugay, Nihan; Kennedy, Joseph P.
ABSTRACT: We describe the discovery of novel low cost bifunctional initiators 2, 4, 7, 9‐tetramethyl‐tricyclo[6.2.0.0 36 ]deca‐1(8), 2, 6‐triene‐4, 9‐diol (bBCB‐diOH) and 4, 9‐dichloro, 2, 4, 7, 9‐tetramethyl‐tricyclo[6.2.0.0 36 ]deca‐1(8), 2, 6‐triene (bBCB‐diCl), for living cationic bidirectional polymerization of olefins, for example, isobutylene. bBCB‐diOH was quantitatively synthesized in one step by UV radiation of commercially available diacetyl durene (DAD) and bBCB‐diCl by hydrochlorination of bBCB‐diOH. These molecules, in conjunction with TiCl4 coinitiator, initiate the living polymerization of isobutylene. Livingness was demonstrated by linear conversion versus molecular weight (MW) plots and narrow MW distributions. Polymerizations are slower than those initiated by the universally used "hindered" bifunctional initiator 5‐tert‐butyl‐1, 3‐bis(1‐chloro‐1‐methyl)benzene and are suitable for rate studies. Herein, we report the synthesis, by the use of bBCB‐diCl, of relatively low MW ( M n < 3000 g mol −1 ) allyl‐telechelic polyisobutylene (PIB) used for the synthesis of PIB‐based polyurethanes and that of relatively high MW ( M n > 30, 000) living PIB telechelics for the synthesis of thermoplastic elastomers. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 3716–3724 Abstract : Two novel bifunctional molecules were designed and synthesized, serving as initiators for the living bi‐directional polymerization of isobutylene. These new initiators are significantly less expensive than the "hindered" initiator universally used for the preparation of telechelic polyisobutylenes.